2016
DOI: 10.7906/indecs.14.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Institutions, Education and Innovation and their Impact on Economic Growth

Abstract: The aim of this article is to provide a closer look of the institutions, their development, education and innovation and their impact on economic growth. The postulates of the neo-classical economic growth theories consider the accumulation of human capital and the technological development as factors that promote economic growth. Thus, investing in education, R&D and innovation is essential for a country's prospects for economic growth. However, the main idea is to present this topic from institutional point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The study went further to depict how economic development was the nexus between innovation, human capital, and institutions. Other studies corroborated these findings by concluding that academic institutions, in particular, contribute to economic development and remain an integral part of innovation (Meek et al, 2010;Oluwatobi et al, 2014;Marić & Kristina, 2016;Nübler, 2016).…”
Section: Literature Reviewmentioning
confidence: 88%
See 1 more Smart Citation
“…The study went further to depict how economic development was the nexus between innovation, human capital, and institutions. Other studies corroborated these findings by concluding that academic institutions, in particular, contribute to economic development and remain an integral part of innovation (Meek et al, 2010;Oluwatobi et al, 2014;Marić & Kristina, 2016;Nübler, 2016).…”
Section: Literature Reviewmentioning
confidence: 88%
“…Ukwuoma (2015) concluded that inculcating indigenous African education results in better quality and performance. In addition, it was noted that essentially, education remains of particular importance in innovation because it creates an avenue for sophisticated innovation, particularly in the field of science and technology (Marić & Kristina, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%